Analyzing the impact of financial development, human capital and industrial structure on ecological footprints: a PMG-ARDL approach - Fairtown Zhou Ayoungman; Abid Hossain Shawon; Ali Sohail (Humanities & Social Sciences Communications)
Abstract Governments worldwide are increasingly focused on balancing economic growth and environmental preservation. For developing economies, achieving sustainable growth while reducing their ecological footprint (EF) is more critical than ever. However, despite notable economic progress, many of these nations continue to face significant challenges in mitigating their environmental impact. In light of this, this research examines the relationship between financial development (FD), human capital (HC), renewable energy consumption (REC), industrial structure (IS), and economic growth (GDP) in relation to the EF across 22 Asian nations from 2000 to 2021. To ensure robust and reliable results, the study employs the pooled mean group-autoregressive distributed lag (PMG-ARDL) approach. The results highlight that REC and HC are crucial drivers of reducing the EF in the long-run, with FD playing a supportive role when combined with HC. GDP has mixed effects on the environment: it initially harms the environment but has a positive long-term effect, supporting the environmental kuznets curve (EKC) hypothesis. The IS requires careful management to shift from being a source of ecological stress in the short-run to contributing positively in the long-run. Based on the results, policymakers in developing nations should prioritize integrating FD, renewable energy adoption, and HC investment to effectively reduce the EF and promote sustainable growth.